Pengaruh Persepsi Dan Preferensi Konsumen Terhadap Keputusan Pembelian Pada Rancamaya Golf And Country Club - Seli Marselina; Sulistiono Sulistiono; Charles Parnauli Saragi (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
The Purpose of this study was to determine (1) the effect of consumer perceptions on their decision on Purchasing at Rancamaya Golf and Country Club, (2) the effect of Consumer Preferences on their decision on Purchasing at Rancamaya Golf and Country Club, (3) the effect of perception and consumer preferences on Purchasing Decisions at Rancamaya Golf and Country Club. The sample consisted of 85 people who were selected using the Slovin technique, taken from the member of Rancamaya Golf and Country Club. All calculations were carried out by using the SPSS 25. The discriminant analysis results show that (1) the consumer perceptions variable has an effect on decision Purchasing at Rancamaya Golf and Country Club. It means the test results support the H1 research hypothesis, the hypothesis H1 is accepted, (2) the Consumer Preferences has an effect on decision Purchasing at Rancamaya Golf and Country Club, the hypothesis H1 is accepted, (3) The results of the F-test study show the calculated of F value or the prob value (0.000) <alpha 5%, then the H0 is rejected, it means that the consumer perceptions (X1) and Consumer Preferences (X2) have an effect on the decision Purchasing at Rancamaya Golf and Country Club (Y). The test results support the research hypothesis H1: β1, β2 ≠ 0 (there is a relationship between X and Y), it means that the Consumer Perceptions and Consumer Preferences variables have a simultaneously effect on Purchasing Decisions. Keywords: Perception, consumer preferences, purchasing decisions